The Road to Serfdom - Hayek, Friedrich (The Institute of Economic Affairs, 2005)
In The Road to Serfdom, the author set out the danger posed to freedom by attempts to apply the principles of wartime economic and social planning to the problems of peacetime...With trademark brilliance, Hayek argues convincingly that, while socialist ideals may be tempting, they cannot be accomplished except by means that few would approve of. Addressing economics, fascism, history, socialism and the Holocaust, Hayek unwraps the trappings of socialist ideology. He reveals to the world that little can result from such ideas except oppression and tyranny.
Keywords: Economic Theory; Non-Fiction